Does the upwelling phenomenon influence the population dynamics and management of the seabob shrimp Xiphopenaeus kroyeri (Heller, 1862) (Crustacea, Penaeidae)? - Davanso, T. M. [UNESP]; Hirose, G. L.; Herrera, D. R. [UNESP]; Fransozo, A. [UNESP]; Costa, R. C. [UNESP] (Springer Nature, 2017)
The seabob shrimp Xiphopenaeus kroyeri ranks third in commercial importance among fisheries in southeastern Brazil. An important management question is whether the same offseason can be applied to different regions. The population dynamics of the seabob shrimp was compared in two regions of southeastern Brazil: Macaé, state of Rio de Janeiro and Ubatuba, state of São Paulo. All demographic categories of shrimp in the Macaé region were larger than those in the Ubatuba region. Lower temperatures and greater longevities in the Macaé region may account for this difference in size from Ubatuba. In Macaé, number of reproductive females and juveniles correlated with organic-matter content. In Ubatuba, only chlorophyll-a showed a correlation with reproductive females. The reproductive period and recruitment were correlated in both populations. The difference in environmental factors between these regions, resulting of the Cabo Frio upwelling, although they are located close together, directly influences the population dynamics of X. kroyeri. The Cabo Frio upwelling may be acting as a physical barrier, preventing gene flow and differentiating the seabob shrimp stocks in the two regions. These data suggest that different offseason periods for different regions could increase the sustainability of shrimp harvesting along the Brazilian coast.
Keywords: Decapoda; Growth; Reproduction; Sustainable harvesting; Upwelling